2018
DOI: 10.3390/socsci7020025
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Quality Education by Understanding Teacher Job Satisfaction Determinants

Abstract: Abstract:The issue of quality education in Nigeria has come up in a number of studies. In particular, the teacher has been identified as a major resource in achieving the very important objective of quality basic education. This comes against the backdrop that teachers are perceived to be in a better position to influence the performance of learners. However, how can they positively influence student performance if they themselves are not motivated? A total of 547 teachers in 23 schools (pre-nursery to senior … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 35 publications
0
20
0
1
Order By: Relevance
“…The results of the present work indicate that proactive human resources policies may be required to protect the newly hired and less experienced teachers from burnout. Personality traits, age, experience, and working conditions can mediate the effect of job characteristics on job satisfaction [54][55][56][57][58][59][60][61]. In turn, unsatisfied teachers may gradually develop negative emotions for their job and be emotionally exhausted [62,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the present work indicate that proactive human resources policies may be required to protect the newly hired and less experienced teachers from burnout. Personality traits, age, experience, and working conditions can mediate the effect of job characteristics on job satisfaction [54][55][56][57][58][59][60][61]. In turn, unsatisfied teachers may gradually develop negative emotions for their job and be emotionally exhausted [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Emotional exhaustion is a precursor to depersonalization, which subsequently can lead to lack of personal accomplishment [34,55]. Burnout can lead to decreased job performance, lack of enthusiasm and commitment, and reduced job satisfaction [55][56][57][58][59][60][61][62]. Educational policy makers could initiate mentoring or aiding initiatives that may be employed to assist teachers in developing skills.…”
Section: Discussionmentioning
confidence: 99%
“…The survey also was done by Iwu et al (2017). The independent factors are job properties and the job qualities, the conditions of auxiliary work: Leadership, supervision, status, job title, interpersonal relationship, reward, recognition, and growth opportunities.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, some notable scholars on TEQ (Rice, 2003;Goe, 2007;Heck, 2007;Akinfe et al, 2012;Adeyemi & Adu, 2012;Duze, & Ogbah, 2013;Edinyang, Opoh & Odey, 2014;Fasasi & Ojo, 2014;Akpanobong & Asuquo, 2015;Daluba, 2015;Okoli, Ogbondah & Ekpefa-Abdullahi, 2015;Josiah & Oluwatoyin, 2017) found that TEQ has significant relationship with SAP. On top of this, school should build more on the quality of teachers so that students' performance can be improved (Ajeyalemi 2013;Adu, Akinloye & Adu, 2015;Josiah & Oluwatoyin, 2017;Tella, 2017;Iwu et al, 2018).…”
Section: The Relationship Between Teacher Quality (Teq) and Students'mentioning
confidence: 99%
“…In the context of transformation, teachers see empowerment as a thing that can improve productivity for them. Although the qualities the teachers possess is not adequately enough to teach students in the classroom (Taiwo, 1980;Musa, Jimba, & Ogundele, 2015;Iwu, Ezeuduji, Iwu, Ikebuaku, & Tengeh, 2018), it is teachers who know the problems facing their students when they are in the classroom. The policy makers and principal do not know what is going on between teacher and students but they decide for the teachers.…”
Section: Introductionmentioning
confidence: 99%